Production of polyclonal antisera using recombinant coat proteins of Grapevine leafroll‑associated virus 2 and Grapevine virus B - Radaelli, Paula; Fajardo, Thor Vinícius Martins; Nickel, Osmar; Eiras, Marcelo; Pio-Ribeiro, Gilvan (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to produce and characterize specific antisera against Brazilian isolates of Grapevine leafroll-associated virus 2 (GLRaV-2) and Grapevine virus B (GVB), developed from expressed coat proteins (CPs) in Escherichia coli, and to test their possible use for the detection of these two viruses in diseased grapevines. The coat protein (CP) genes were RT-PCR-amplified, cloned and sequenced. The CP genes were subsequently subcloned, and the recombinant plasmids were used to transform E. coli cells and express the coat proteins. The recombinant coat proteins were purified, and their identities were confirmed by SDS-PAGE and Western blot and used for rabbit immunizations. Antisera raised against these proteins were able to recognize the corresponding recombinant proteins in Western blots and to detect GLRaV-2 and GVB in infected grapevine tissues, by indirect ELISA, discriminating healthy and infected grapevines with absorbances (A405) of 0.08/1.15 and 0.12/1.30, respectively. Expressing CP genes can yield high amount of viral protein with high antigenicity, and GLRaV-2 and GVB antisera obtained in this study can allow reliable virus disease diagnosis.